Fatores associados à vacinação contra a influenza em idosos - Francisco, Priscila Maria Stolses Bergamo; Donalisio, Maria Rita; Barros, Marilisa Berti de Azevedo; César, Chester Luis Galvão; Carandina, Luana [UNESP]; Goldbaum, Moisés (FapUNIFESP (SciELO), 2006)
Objective. To investigate the epidemiologic profile of elderly persons who do or do not participate in influenza vaccination campaigns and to identify the variables that bear an influence on participation. Method. A cross-sectional population-based study was performed using data on individuals aged 60 years or older who were living in the municipalities of São Paulo, Itapecerica da Serra, Embu, Taboão da Serra, Campinas and Botucatu, Brazil, in 2001 and 2002. A stratified random sample of 1 908 elderly individuals was selected by means of two-stage cluster sampling. Exploratory data analysis was performed, including bivariate analysis and multiple logistic regression. Results. Sixty-six percent of the elderly subjects reported having received vaccination against influenza. After adjustment, the following factors were found to be associated with having received vaccination, based on self-report: age (OR = 1.47; 95% CI = 1.09 to 1.99), self-reported hypertension (OR = 1.39; 95% CI = 1.03 to 1.87) and educational level (OR = 0.64; 95% CI = 0.41 to 0.98). The highest number of vaccinated individuals was observed in the group = 70 years of age and in the hypertension group. Individuals with 9 or more years of schooling reported less adherence to influenza vaccination. Conclusions. The results suggest the need for campaigns to make information on the benefits of influenza vaccination more easily accessible to the elderly and health professionals.
Factors associated with vaccination against influenza in the elderly
Keywords: Aging health; Brazil; Disease susceptibility; Influenza; Vaccination; cross section; epidemiology; influenza; vaccination; adult; aged; controlled study; data analysis; education; factorial analysis; female; health education; human; human experiment; hypertension; influenza vaccination; male; multivariate analysis; multivariate logistic regression analysis; population based case control study; Africa; Botucatu; Campinas; East Africa; Eastern Province [Kenya]; Embu; Kenya; Sao Paulo [Brazil]; South America; Sub-Saharan Africa